Iconicity in Signed and Spoken Vocabulary: A Comparison Between American Sign Language, British Sign Language, English, and Spanish - Perlman, Marcus; Little, Hannah; Thompson, Bill; Thompson, Robin L. (Frontiers in Psychology, 2018)
Considerable evidence now shows that all languages, signed and spoken, exhibit a significant amount of iconicity. We examined how the visual-gestural modality of signed languages facilitates iconicity for different kinds of lexical meanings compared to the auditory-vocal modality of spoken languages. We used iconicity ratings of hundreds of signs and words to compare iconicity across the vocabularies of two signed languages – American Sign Language and British Sign Language, and two spoken languages – English and Spanish. We examined 1) the correlation in iconicity ratings between the languages; 2) the relationship between iconicity and an array of semantic variables (ratings of concreteness, sensory experience, imageability, perceptual strength of vision, audition, touch, smell and taste); 3) how iconicity varies between broad lexical classes (nouns, verbs, adjectives, grammatical words and adverbs); and 4) between more specific semantic categories (e.g. manual actions, clothes, colors). The results show several notable patterns that characterize how iconicity is spread across the four vocabularies. There were significant correlations in the iconicity ratings between the four languages, including English with ASL, BSL, and Spanish. The highest correlation was between ASL and BSL, suggesting iconicity may be more transparent in signs than words. In each language, iconicity was distributed according to the semantic variables in ways that reflect the semiotic affordances of the modality (e.g. more concrete meanings more iconic in signs, not words; more auditory meanings more iconic in words, not signs; more tactile meanings more iconic in both signs and words). Analysis of the 220 meanings with ratings in all four languages further showed characteristic patterns of iconicity across broad and specific semantic domains, including those that distinguished between signed and spoken languages (e.g. verbs more iconic in ASL, BSL, and English, but not Spanish; manual actions especially iconic in ASL and BSL; adjectives more iconic in English and Spanish; color words especially low in iconicity in ASL and BSL). These findings provide the first quantitative account of how iconicity is spread across the lexicons of signed languages in comparison to spoken languages.